Systematic literature review on slow/ controlled release fertilizers (SCRF) material: fabrication methods, characteristics, nutrient release, and crop yield effects - Suci Setia Crise Manullang; Fitri Khoerunnisa (Acta Chimica Asiana, 2026)
Slow/controlled-release fertilizers (SCRF) are increasingly adopted to improve nutrient-use efficiency and reduce environmental losses amid fertilizer price volatility and sustainability demands. This systematic literature review synthesizes recent SCRF evidence by linking fabrication methods, material characteristics, nutrient release behavior, and agronomic outcomes. A structured search was conducted in ScienceDirect for open-access English research articles published between 2021–2025, focusing on urea-based SCRF that reported material composition/characterization, nutrient release profiles, soil indicators, and/or crop productivity. Thirty-eight studies met the inclusion criteria. The SCRFs were grouped into five material classes: synthetic polymers, natural/biobased polymers, biochar-based composites, inorganic minerals, and inhibitor/multifunctional systems. Fabrication was dominated by coating/encapsulation and blending to form core–shell granules (common in synthetic polymers), while polymerization, cross-linking, and casting frequently produced hydrogels or porous 3D networks (typical of biopolymers). Across studies, surface chemistry (hydrophobic versus hydrophilic functional groups) and coating integrity governed water ingress and release mechanisms (diffusion-barrier release versus swelling/degradation-assisted release), yet mechanical and swelling reporting remained inconsistent. Overall, SCRF improved crop yields relative to conventional fertilizers, with reported gains ranging from 1.47% to over 100% depending on material type, crop, and trial conditions. Key trade-offs persist between long-duration release precision, cost, and biodegradability, and cross-study comparison is limited by non-uniform biodegradation tests. Several papers assessed nitrogen-use efficiency and soil indicators (e.g., leaching or gaseous losses), but protocols and reporting units varied. Incorporating inhibitors or mineral fillers can further extend release, yet may increase persistence risks and complicate environmental fate assessment. Future work should standardize performance metrics and develop hybrid designs that balance release control, durability, and environmental fate.